Assessment of the physico-nutritional effects and pathogen detection in kangkong (Ipomoea reptans) grown in used vermicomposts-amended soil - Carinal , Limalyn Joy L.
The physico-nutritional attributes and presence of pathogens in kangkon (Ipomoea reptans) grown in used Vermicompost-amended soil were assessed in a pot experiment in the greenhouse during late 2004 wet season.